Organisational justice, human resource development, organisational t rust and employee engagement : a case of Pan-Afric Impex Limited Uga nda - Nakisita, Victoria (Kampala, 2013)
Unpublished dissertation (MBA) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Organisational justice -- Uganda; Personnel management -- Uganda; Education -- Uganda